The effect of different finishing & polishing protocols on the surface roughness & flexural strength of zirconia bars - Fatima AlBishry; Dana Qeblawi; Joseph Rumfola; Elaine Davis (Elsevier, 2019)
Introduction: The aim of this study is to evaluate the effect of three different finishing and polishing protocols on the surface roughness and flexural strength of tetragonal zirconia. Materials and methods: 1: Surface roughness; One hundred and five bars of Y-TZP were prepared from Zenostar zirconia blocks (Ivoclar Vivadent). Fifteen bars were distributed into one of seven groups (n = 15/group). Three rotary systems were assessed for finishing and polishing zirconia. After surface preparation the surface roughness was measured using a non-contact profilometer (NPFlex Light interferometer, Bruker Corp., Tucson, AZ). 2: Flexural Strength; Flexural strength of the bars was determined using a three point bending test in a Universal Testing Machine (Instron). Results: 1: Surface roughness; A significant interaction was demonstrated between grinding condition and polishing kit (P = 0.001). 2: Flexural Strength; a statistically significant difference in flexural strength between groups was seen (p < 0.05). There was no significant interaction effect (P = 0.869). Conclusions: Surface adjustment with dry grinding conditions increased the surface roughness of Y-TZP using the Komet polishing kit compared to wet conditions. Dry grinding lowered the flexural strength compared to wet grinding, irrespective of the kit being used. Achieving a polished surface comparable to that of the control group can be possible by using Brasseler's zirconia polishing kit under wet grinding conditions.